2009
DOI: 10.4081/815
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cancer clones in human gastric adenoma by increased DNA-instability and other biomarkers

Abstract: An immunohistochemical differential staining of cancerous cells with anti-cytidine antibody after denaturation of nuclear DNA by acid hydrolysis with 2N HCl at 30°C for 20 min (DNA-instability test) has been used as a marker of malignancy. The test was applied to bioptic tissues of human gastric polyp assessed histopathologically as foveolar hyperplastic polyp (13 cases), mild (58 cases), moderate (86 cases), and severe (20 cases) dysplasia, and adenocarcinomas (14 cases). The serial sections of the same tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Induction of DFF45 seems to be involved in the production of heterogenous subclones in human gastric cancer cells, and in their enhanced ability to avoid apoptosis [35]. Hara et al found that when DFF45 is overexpressed in human renal cell carcinoma cells, it renders them highly resistant to therapy-induced apoptosis [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Induction of DFF45 seems to be involved in the production of heterogenous subclones in human gastric cancer cells, and in their enhanced ability to avoid apoptosis [35]. Hara et al found that when DFF45 is overexpressed in human renal cell carcinoma cells, it renders them highly resistant to therapy-induced apoptosis [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…From a Western point of view, the final diagnosis rests on examination of the surgical or ESD specimen, because there is some possibility of cancer even if the diagnosis is LGD or HGD [21,23,36,[46][47][48]. Some studies have indicated that LGD and HGD should be treated, because genomic instability may already be present [49][50][51][52]. However, the European guidelines recommend reassessment with biopsy sampling and surveillance at 6-month to 1-year intervals for patients with HGD in the absence of endoscopically defined lesions [8].…”
Section: Discussionmentioning
confidence: 99%